Digital influence on consumer habits : marketing challenges and opportunities - Singh, Nripendra; Kansra, Pooja; Gupta, S. L. (Emerald Publishing Limited, 2024)
Customers are now highly influenced by digital marketing and ease of purchase, level of service, technological security, and returns processes. Electronic word of mouth (eWOM) has become the biggest persuader of consumer retention and attracting new customers, with websites frequently judged by their simplicity. For any business it has become imperative to understand the various factors which influence the customers to purchase through digital modes, and the authors undertake a thorough analysis of these factors in Digital Influence on Consumer Habits. The chapters look at Artificial Intelligence, trend setting and the impact of social media, the effect of the COVID-19 pandemic on various sectors, and much more. Readers will learn service quality, peer pressure, online reviewers' effect in the digital environment to aid in understanding the various risks and challenges involved in the digital environment, with examples of changing business and consumer scenario case studies as a result of Digital Transformation.
Includes index.
Keywords: Internet marketing.; Consumer behavior.; Consumption (Economics); Business & Economics -- Marketing -- General.; Online marketing / Social media marketing.; Sales and marketing.; elektronické knihy; electronic books